Building Flex 4 app with Spark components - Braithwaite, Garth (O'Reilly breakdown., 2010)
"Adobe Flex is a strong tool for creating data centric Rich Internet Applications. With the advent of Flex 4, it has become easier to customize the design of your Flex application and control the user experience. The Flex team also focused on reducing development time and taking advantage of the latest features in Flash Player 10. Why is there a need for this video? Although Flex is powerful, there is a barrier to entry as it there isn't another development environment just like it. Given the freedom allowed in Flex it is easy to pick up bad inefficient practices. Flex 4 is a major shift from previous versions making it hard to know which practices still work. Audience: ActionScript Developers looking to expand their knowledge to Flex. Flex 3 developers looking to make the jump to Flex 4"--Resource description page.